Jejunal intussusception as a rare cause of newborn bowel obstruction - Haris Muhammad; Joseph C L'Huillier; Ruchi Amin; Phillip Benson Ham, III (Elsevier, 2022)
Neonatal intussusception is a rare cause of intestinal obstruction in the neonate, particularly in a newborn. It can present similar to necrotizing enterocolitis (NEC), with findings such as abdominal distension, feeding intolerance, and gastrointestinal bleeding. This often results in delayed diagnosis leading to increased morbidity and mortality. For jejunal intussusception, non-operative reduction may be attempted, but is not often successful, so surgical intervention is usually required. While newborn presentation is out of the typical age for idiopathic intussusception without a lead point and a lead point should be assessed for, it may be idiopathic. Although rare, intussusception should be in the differential for bowel obstruction in the neonatal period. X rays and contrast studies may suggest obstruction and it can be reliably diagnosed with abdominal ultrasound (US). We present a case of an early near term neonate presenting with bilious emesis in first 24 hours of life, with contrast studies concerning for proximal obstruction, who on surgical exploration was found to have an isolated jejuno-jejunal intussusception.